1996
DOI: 10.1021/jp952525x
|View full text |Cite
|
Sign up to set email alerts
|

Redox Behavior of CuZSM-5 Catalysts:  FTIR Investigations of Reactions of Adsorbed NO and CO

Abstract: The redox behavior of CuZSM-5 was investigated by flow microbalance and FTIR measurements using CO and NO as probe molecules. The weight change resulting from switching the flow of 10% O2 in He to pure He corresponded to the removal of extralattice oxygen and approximately 20% autoreduction of total copper ion by one electron. FTIR absorption spectra of CO over CuZSM-5 showed that the concentration of the Cu+ sites changed reversibly upon switching the pretreatment gas from He to O2. The combined experiments (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
100
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(102 citation statements)
references
References 42 publications
2
100
0
Order By: Relevance
“…[4][5][6][7] The expected presence of such species, together with electron spin resonance and thermogravimetric studies, 7 suggest that redox cycles are responsible for NO decomposition turnovers. Infrared spectra of adsorbed CO and NO provided indirect evidence for the reversible cycling between Cu 2+ and Cu + during switching between O 2 and He streams at 773 K. 8 These cycles were confirmed by X-ray photoelectron (XPS) and X-ray absorption (XAS) spectroscopic studies. 9 The parallel increase in the concentration of Cu + species detected by XAS and in the rate of NO decomposition was used as evidence for Cu + as a reaction intermediate.…”
Section: Introductionmentioning
confidence: 85%
“…[4][5][6][7] The expected presence of such species, together with electron spin resonance and thermogravimetric studies, 7 suggest that redox cycles are responsible for NO decomposition turnovers. Infrared spectra of adsorbed CO and NO provided indirect evidence for the reversible cycling between Cu 2+ and Cu + during switching between O 2 and He streams at 773 K. 8 These cycles were confirmed by X-ray photoelectron (XPS) and X-ray absorption (XAS) spectroscopic studies. 9 The parallel increase in the concentration of Cu + species detected by XAS and in the rate of NO decomposition was used as evidence for Cu + as a reaction intermediate.…”
Section: Introductionmentioning
confidence: 85%
“…Most of the cases concern Cu ϩ cations in zeolites, where a band assigned to adsorbed dinitrogen has been detected in the 2299-2290-cm Ϫ1 region [32,[129][130][131]. Most of the cases concern Cu ϩ cations in zeolites, where a band assigned to adsorbed dinitrogen has been detected in the 2299-2290-cm Ϫ1 region [32,[129][130][131].…”
Section: Identification Of N X O Y Species 75mentioning
confidence: 99%
“…12 These were the only infrared bands detected at 673 K. Infrared studies have also confirmed that NO adsorbs on Cu + 5,13-18 and suggested that Cu + /Cu 2+ redox reactions occur as conditions change from reducing to oxidizing. 19 NO decomposition appears to occur via the initial formation of N 2 O followed by its decomposition. 26 N 2 O and small amounts of N 2 are typically detected during temperature-programmed desorption of preadsorbed NO on Cu-ZSM5.…”
Section: Introductionmentioning
confidence: 99%